2020
DOI: 10.1111/acer.14518
|View full text |Cite
|
Sign up to set email alerts
|

The “Why” of Drinking Matters: A Meta‐Analysis of the Association Between Drinking Motives and Drinking Outcomes

Abstract: Background Knowledge of how drinking motives are differentially associated with alcohol use (e.g., frequency, quantity) and drinking problems is critical in understanding risky drinking and the development of alcohol use disorder. The purpose of this paper was to use meta‐analytic techniques to answer 2 overarching questions: (a) Which types of drinking motives (i.e., enhancement, coping, social, conformity) are most strongly associated with alcohol use and drinking problems? and (b) What are the most likely m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
67
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 55 publications
11
67
1
Order By: Relevance
“…Results from this study indicate that, for both men and women, stronger coping and social motives for drinking early in the pandemic predicted an initial higher average level of alcohol use, whereas only stronger coping motives predicted an initial higher average level of alcohol problems. This is consistent with results from a recent meta-analysis which found that both coping and social motives for drinking were positively associated with drinking; however, drinking for coping reasons was the stronger predictor of drinking problems ( Bresin and Mekawi, 2021 ). Further, for women, higher social motives for drinking early in the pandemic predicted an increase in their alcohol problems over time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results from this study indicate that, for both men and women, stronger coping and social motives for drinking early in the pandemic predicted an initial higher average level of alcohol use, whereas only stronger coping motives predicted an initial higher average level of alcohol problems. This is consistent with results from a recent meta-analysis which found that both coping and social motives for drinking were positively associated with drinking; however, drinking for coping reasons was the stronger predictor of drinking problems ( Bresin and Mekawi, 2021 ). Further, for women, higher social motives for drinking early in the pandemic predicted an increase in their alcohol problems over time.…”
Section: Discussionsupporting
confidence: 91%
“…Past research on both young people and older adults indicates that these motives include coping motives (drinking to attenuate negative emotions, such as to cheer up or forget one’s problems) and social motives (drinking to obtain positive social outcomes, such as to be more sociable or enjoy social gathering) ( Cooper et al, 2016 , Gilson et al, 2013 ). A recent meta-analysis of 229 studies, the vast majority being cross-sectional, found that both types of motives were positively and significantly associated with drinking frequency, quantity, and problems ( Bresin and Mekawi, 2021 ). Recent work has shown the relevance of drinking motives for alcohol use during COVID-19 pandemic as well.…”
Section: Introductionmentioning
confidence: 99%
“…This way of thinking about drivers of alcohol consumption may have wider theoretical implications. For example, when considering the drinking motives literature [ 144 , 145 ]—which is also characterised by inconsistent and mixed finding (although see meta-analysis by [ 146 ])—it may be possible to think about distinct emotional drinking motive categories (enhancement and coping, [ 147 ]) in terms of ‘affect regulation’. In this way, Littlefield et al found that drinkers who consume alcohol for either coping or enhancement motives do not form two distinct groups [ 14 ], suggesting that these motives may be best viewed as dimensional variables that covary such that individuals who are high in one internal motive tend to be high in the other motive.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the motivational model of alcohol use (Cox & Klinger, 1988) considers positive and negative incentives in its theoretical framework and suggests incentives specific to a situation play a major role in expectancies, motives, and affect related to drinking (see Cox & Klinger, 1988). Indeed, a rich body of literature has examined motives of substance use (Bresin & Mekawi, 2021; Cox & Klinger, 1988; Votaw & Witkiewitz, 2021) which primarily reflect personal reasons to drink (Cooper, 1994) while not always considering decision incentives that may reflect event ‐specific reasons to decide to drink or attend a drinking event. For example, research of drinking motives typically asks participants “How frequently is your drinking motivated by the following reasons?” or “Please rate how important each item is to you as a reason for drinking” (Cooper, 1994; Votaw & Witkiewitz, 2021), which do not fully assess the influence and varying presence of event‐specific incentives on the participant's decision to drink as originally theorized by Cox and Klinger (1988).…”
Section: Introductionmentioning
confidence: 99%